Multivariable Predictive Control of the Main Steam Temperature in Power Plant - Wang Ting; Feng Xiaolu; Chen Jiangtao; Zhang Rong; Xu Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper aims at the problems existing in the cascade Proportional Integration Differential (PID) control of the main steam temperature system in power plants nowadays, such as large dynamic deviation, poor load adaptability. etc. The two multivariable model predictive controllers are designed and applied to control the second stage desuperheater inlet temperature and the main steam temperature, respectively, which is aimed by the simulation platform for 200 MW unit. The controlled object of the main steam temperature is simulated, and both predictive control and cascade PID control strategies are designed to control the object. The results of the stimulation experiments have shown that the predictive controller is superior to the traditional cascade PID controller in dynamic deviation and load adaptability of main steam temperature in power plant. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2376